Cast away [videorecording (Blu-Ray)] - Starkey, Steve; Hanks, Tom; Hanks, Tom; Zemeckis, Robert, 1952-; Zemeckis, Robert, 1952-; Rapke, Jack; Broyles, William, Jr., 1944-; Hunt, Helen, 1963-; Searcy, Nick (20th Century Fox Home Entertainment, 2008)
Chuck Noland is a FedEx systems engineer whose personal and professional life are ruled by the clock. His fast-paced career takes him to many different locations, causing him to be away from his girlfriend Kelly. Chuck's life is abruptly changed when, after a plane crash, he becomes stranded on a remote island. Now, stripped of the conveniences of everyday life, he first must meet the basic needs of survival, including water, food and shelter. Chuck, who is the consummate problem solver, eventually figures out how to sustain himself physically. After four years, fate gives Chuck a chance to fight his way back to civilization. He does so, but only to find an unexpected emotional challenge greater than all the earlier physical ones. His ability to persevere and to hope are a product of his life-changing experience.